The role of the pathologist in the multidisciplinary management of human papilloma virus-associated head and neck cancer. Issue 2 (February 2015) - Helliwell, Tim
Abstract The recognition of a subset of oropharyngeal carcinomas in which the neoplastic process is driven by human papillomaviruses (HPV) has important implications for patients and clinicians. The increasing incidence challenges clinical services at a time when smoking and alcohol related malignancies are becoming fewer. For patients, HPV-associated carcinomas have a relatively good prognosis and there is the prospect that treatment may be less intensive without compromising the outcome. The use of individually targeted therapies is determined by the availability of tumour-specific biomarkers. The challenge for pathologists is to ensure that testing protocols provide accurate, reproducible and timely advice for clinicians and patients to make informed decisions. A combination of immunocytochemical assessment of p16 expression and in situ hybridisation for high risk HPV DNA provides acceptable sensitivity and specificity. Recruitment to clinical trials for oropharyngeal carcinomas requires assessment of HPV status using routine methodologies but, in future, other molecular methods may be required.